Impairment of prosocial sentiments is associated with frontopolar and septal damage in frontotemporal dementia - Moll, Jorge (2010)
Poets and philosophers have long acknowledged moral sentiments as key motivators of human social behavior. Prosocial sentiments, which include guilt, pity and embarrassment, enable us to care about others and to be concerned about our mistakes. Functional imaging studies have implicated frontopolar, ventromedial frontal and basal forebrain regions in the experience of prosocial sentiments. Patients with lesions of the frontopolar and ventromedial frontal areas were observed to behave inappropriately and less prosocially, which could be attributed to a generalized emotional blunting. Direct experimental evidence for brain regions distinctively associated with moral sentiment impairments is lacking, however. We investigated this issue in patients with the behavioral variant of frontotemporal dementia, a disorder in which early and selective impairments of social conduct are consistently observed. Using a novel moral sentiment task, we show that the degree of impairment of prosocial sentiments is associated with the degree of damage to frontopolar cortex and septal area, as assessed with 18-Fluoro-Deoxy-Glucose-Positron Emission Tomography, an established measure of neurodegenerative damage. This effect was dissociable from impairment of other-critical feelings (anger and disgust), which was in turn associated with dorsomedial prefrontal and amygdala dysfunction. Our findings suggest a critical role of the frontopolar cortex and septal region in enabling prosocial sentiments, a fundamental component of moral conscience.